Aspectos epidemiológicos do melanoma no serviço de dermatologia do hospital das clínicas da universidade federal de minas gerais, 1990-2010 - Flavia Vieira Brandao (2011)
INTRODUCTION: During the last decades the incidence of cutaneous melanoma has systematically increased. Althoug it accounts for only 3% of all skin cancers, it is responsible for 75% of the deaths. Early recognition represents the only chance of cure. We didnt find in literature any epidemiological studies of cutaneous melanoma in the state of Minas Gerais, Brazil. METHODS: A total of 166 patients were analyzed between January 1990 and January 2010 for clinical variables (sex, age, skin color, localization, atypical nevus, nonmelanoma skin-cancer, noncutaneous cancer, family history of melanoma, signs and/or symptoms, metastases and deaths related to melanoma) and histological variables (histological type, depth of invasion and Clark level) and correlations between them. A significant level of 0.05 was adopted. RESULTS: Females predominated (61%) and the mean age of diagnosis was 55 years. Most patients (74%) were Caucasians. A family history of melanoma was present in 10% of all cases and atypical nevi were found in almost 20%. Nonmelanoma skin cancer was reported in 27.7%. The histological type more prevalent was lentigo maligna/lentigo maligna melanoma and the most frequent localization of cutaneous melanoma in head and neck. As to gender and site of primary lesion, women were most affected in the extremities and men in head and neck and trunk. The majority of tumors were in situ (41%) and thin (31.1%). Lesion growth (58.1%) was the most frequent sign and bleeding was associated with thicker melanomas. There were seven deaths (4.2%) with more risk of death in men, non-white, < 20 years, Breslow > 2mm, lentiginous acral melanoma, history of growth and bleeding. However, after multivariate analysis, only age < 20 years and history of bleeding remained associated with more risk of death. CONCLUSIONS: This sample differs from the great part of the studies in predominant localization (head and neck), histological type (lentigo maligna/lentigo maligna melanoma), proportion of nonmelanoma skin cancer (27.7%) and great risk of deaths in age under 20 years which may reflect regional variation or differences in solar exposure. This study is concordant with literature as to sex predominance (female), age (mean of 55 years), frequency of atypical nevus (almost 20%) and family history of melanoma (10%). Fortunately, following a worldwide trend, a large number of melanomas was early diagnosed (72%) with a small number of deaths (4.2%). Limitations of this study are a small number of cases comparing with population based and multicentric studies, the absence of important histological parameters like ulceration and mitotic rate and the difficulty to classify patients by the color of the skin. Further studies are necessary for validation of the results.